GLOBALIZATION, HUMAN SECURITY AND SOME INTERVENING CONCERNS - Olufemi Oludimu (European Scientific Journal, ESJ, 2014)
Traditionally the concept of “security” has been couched in neo-realist terms, relating to protecting the territorial integrity and political sovereignty of nations. This continues to be a legitimate concern for scholars and policy-makers alike, but at the current state of human development it is clear that an alternative or even complimentary conception of “security” needs to assume critical importance. A conceptualization of security that is centered primarily on the individual or community can be understood as human security. This notion grows from the assumption that there are needs, problems, and issues that are common to all of mankind no matter what part of the world they live in, for example, poverty; the spread of communicable diseases; environmental degradation; the loss of faith in institutions; population pressures; and economic crisis. It is imperative that we view these concerns in terms of global trends and forces that affect the individual. The question then is ; how can we ensure human security? This can be achieved not through force of arms, but through policies that lead to the empowerment of people and an attack on the sources of intervening concerns and contemporary problems as such poverty,migration and income inequality challenges. These issues form the kernel of the present paper. In concluding, the paper proffers suggestions by way of some reversal policies that can mitigate some of the challenges identified so as to ensure improved human security on the global plane.